Question
upstudy study bank question image url

tics Mathematics Grade 12 Learner Material What is the value of \( m \) for which: \[ \sum_{k=1}^{m} 5(3)^{k-1}=65 \] Consider the sequence:

Ask by Chang Gonzalez. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( m = 3 \)

Solution

To determine the value of \( m \) that satisfies the equation: \[ \sum_{k=1}^{m} 5 \cdot 3^{k-1} = 65 \] we can recognize that this sum represents a **geometric series**. Let's break down the solution step-by-step. ### Step 1: Identify the Components of the Geometric Series A geometric series has the general form: \[ S_m = a \cdot \frac{r^m - 1}{r - 1} \] where: - \( S_m \) is the sum of the first \( m \) terms, - \( a \) is the first term, - \( r \) is the common ratio, - \( m \) is the number of terms. For the given series: \[ \sum_{k=1}^{m} 5 \cdot 3^{k-1} \] - **First Term (\( a \))**: When \( k = 1 \), \[ a = 5 \cdot 3^{1-1} = 5 \cdot 3^{0} = 5 \cdot 1 = 5 \] - **Common Ratio (\( r \))**: The ratio between successive terms is \( 3 \) since each term is multiplied by \( 3 \) to get the next term. ### Step 2: Plug the Values into the Sum Formula Using the formula for the sum of a geometric series: \[ S_m = a \cdot \frac{r^m - 1}{r - 1} \] Substitute the known values: \[ 65 = 5 \cdot \frac{3^m - 1}{3 - 1} \] \[ 65 = 5 \cdot \frac{3^m - 1}{2} \] ### Step 3: Solve for \( m \) 1. **Multiply both sides by 2 to eliminate the denominator:** \[ 65 \times 2 = 5 \cdot (3^m - 1) \] \[ 130 = 5 \cdot (3^m - 1) \] 2. **Divide both sides by 5:** \[ \frac{130}{5} = 3^m - 1 \] \[ 26 = 3^m - 1 \] 3. **Add 1 to both sides:** \[ 26 + 1 = 3^m \] \[ 27 = 3^m \] 4. **Find the value of \( m \) such that \( 3^m = 27 \):** Since \( 3^3 = 27 \), \[ m = 3 \] ### Conclusion The value of \( m \) that satisfies the equation is: \[ \boxed{3} \]

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

The Deep Dive

To solve for \( m \), we can recognize this as a geometric series where the first term \( a = 5 \) and the common ratio \( r = 3 \). The sum of the first \( m \) terms of a geometric series is given by: \[ S_m = a \frac{r^m - 1}{r - 1} \] Substituting the values, we have: \[ 65 = 5 \frac{3^m - 1}{3 - 1} \] Simplifying this gives: \[ 65 = \frac{5(3^m - 1)}{2} \] Multiplying through by 2: \[ 130 = 5(3^m - 1) \] Dividing by 5 results in: \[ 26 = 3^m - 1 \] Thus: \[ 3^m = 27 \] Since \( 27 = 3^3 \), we find: \[ m = 3 \] Now let's look at some interesting context behind sequences and series! This type of series finds notable applications in finance, especially in calculating the future value of investments given a consistent rate of return. If you were to invest a certain amount that grows in a compounded fashion (like your sequence), understanding how these terms add up makes a difference in predicting how much you'll have in the future. When working with geometric series, one common mistake is forgetting to correctly identify the first term and the common ratio. Ensuring the accurate input of these values when using the sum formula is crucial – a simple slip can lead to incorrect conclusions. Always double-check the initial conditions before diving into calculations!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy